TO ANALYSE HOW LOCAL FASHION BRANDS ARE BUILDING THEIR BRAND IDENTITY AS A DIFFERENTIATOR IN THE SOUTH AFRICAN MARKET - Hlungwani, Brenda (The IIE, 2022)
Competition within the South African fashion industry has intensified following the influx of global fashion brands in the market (Petzer & De Meyer, 2013, cited in Coetzee, 2018). It is therefore apparent that local fashion brands need to cut through the clutter of a saturated market by differentiating themselves against rival brands. The risk of lacking a distinctive brand identity as a clear differentiator leaves brands vulnerable to potential brand identity confusion amongst their competitors (Srivastava, 2011). There is therefore a need to develop a comprehensive understanding of how local fashion brands are building a distinctive brand identity to stand out in the market. This paper explores how local fashion brands are building their brand identity as a differentiator in the South African market by analysisng the Maxhosa Africa brand, against Aaker’s (1996) Brand Identity Planning Model. The data was collected through semi-structured interviews to understand the perspective of their brand team. The study found that Maxhosa Africa has developed a multifaceted brand identity, consisting of a core and extended identity as suggested by David A. Aaker, which visibly differentiates the brand for easy identification without confusion. This paper makes two main contributions. First, it adds to the current understanding of brand identity development which sits within the brand management literature. And second, it advocates for the importance of developing a distinctive brand identity as a clear differentiator for local fashion brands in the South African market.
AN ANALYSIS OF THE MAXHOSA AFRICA BRAND
Keywords: Culture; Heritage; Digital marketing; Buying patterns; Customer behaviour